(untitled) (International Journal of Engineering and Computer Science, 2021)
Wi Fi and hotspots give remote web climate. With the successive utilization of these, there is a quick increment of dangers to remote AP (Access Point). Correctly when ill conceived AP’s are utilized around affiliations, federal government there’s excessive chance to be assaulted by different viruses as well as hacking strikes. It is important to distinguish the illegitimate access points to stay away from data break. In this paper we have used RTT (Round Trip Time) informational collection to recognize legitimate and illegitimate access points in remote incorporated climate and afterward investigate them utilizing the machine learning algorithm including SVM (Support Vector Machine), KNN (K-Nearest Neighbor) and Decision Tree classifier.